2018
DOI: 10.3390/su10082678
|View full text |Cite
|
Sign up to set email alerts
|

Biogas Potential of Coffee Processing Waste in Ethiopia

Abstract: Primary coffee processing is performed following the dry method or wet method. The dry method generates husk as a by-product, while the wet method generates pulp, parchment, mucilage, and waste water. In this study, characterization, as well as the potential of husk, pulp, parchment, and mucilage for methane production were examined in biochemical methane potential assays performed at 37 • C. Pulp, husk, and mucilage had similar cellulose contents (32%). The lignin contents in pulp and husk were 15.5% and 17.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 32 publications
1
22
0
1
Order By: Relevance
“…50%, with a moisture content of approximately 21%. Similar results were reported by Chala et al [2018], while Cruz and Crnkovic [2015] reported a ratio of 45% : 50%.…”
Section: The Smallholder Coffee Life Cyclesupporting
confidence: 86%
“…50%, with a moisture content of approximately 21%. Similar results were reported by Chala et al [2018], while Cruz and Crnkovic [2015] reported a ratio of 45% : 50%.…”
Section: The Smallholder Coffee Life Cyclesupporting
confidence: 86%
“…This disposal of coffee husks not only wastes biomass energy and land resource, but also causes certain environmental harms such as affecting the soil and water quality (Preethu et al, 2007). According to Chala et al’s (2018) report, from 2007 to 2016, annual coffee production increased from 273,400 ton (t) to 469,091 t, while the planting area increased from 407,147 ha to 700,475 ha. Consequently, the coffee waste grew as the amount of processed coffee cherries increased.…”
Section: Introductionmentioning
confidence: 99%
“…Sugars such as sucrose, glucose and fructose, and organic acids such as lactic acid, formic acid, acetic acid and propionic acid were determined as described by Haag, et al [35]. The chemical characteristics of husks, pulp and mucilage were already presented in detail in a previous study of the authors [36].…”
Section: Chemical Analysismentioning
confidence: 99%